Production of Resistant Starch from Avocado Seeds (Persea americana) through Streptomyces sp. AB8 Fermentation and Autoclaving-Cooling Variations - Achmad Arifiyanto; Siti Inah; Indah Sukma Ningsih; Christina Nugroho Ekowati; Tundjung Tripeni Handayani (Indonesian Journal of Chemical Analysis (IJCA), 2023)
Agricultural waste with a high starch content potentially serves as a source of resistant starch. The avocado seed has not been explored much and is often thrown away as waste in consuming avocados. Resistant starch has properties and functions as dietary fiber and has advantages as a prebiotic. This study aims to determine the effect of fermentation treatment using Streptomyces sp. AB 8 and variations in the number of pressure-cooling heating cycles to increase avocado seed-resistant starch. The research phase consisted of pre-treating the avocado seeds and fermentation by Streptomyces sp. AB 8 followed by a pressure heating-cooling stage with 0, 1, 2, and 3 cycles. Concerning modified starch, this study also measured levels of starch, amylose, amylopectin, and resistant starch. Digestion test using Lactobacillus sp. by viewing the clear zone around the colonies after 48 hours to evaluate the digestibility of resistant starch. The results of this study indicate that the fermentation treatment by Streptomyces sp. AB 8 and pressure-cooling heating can increase the levels of resistant starch in avocado seeds. Fermentation treatment with two cycles of heating-pressure-cooling (S1) produced the best resistant starch content of 7.51% and had the highest enzymatic index of 2.48 ± 0.45.